P-38 EVALUATION OF THE GENETIC AND VIROLOGICAL PROFILE OF PREGNANT WOMEN INFECTED WITH HEPATITIS B AND C VIRUSES IN A REFERENCE CENTER IN RIO DE JANEIRO, BETWEEN 2016 AND 2022 - Kaio Ferreira Callebe Pedro; Vinicius Mello Motta; Giovana Nascimento Guimarães Santos; Giovana Angelice Paula; Paulo Sergio Sousa Fonseca; Aryele Raíra Pereira da Silva; Nathalia Balassiano; Caroline Baldin; Poliana Fernandes; Girleide Oliveira Pereira; Livia Villar Melo; Barbara Lago Vieira; et al. (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: It is estimated that there are around 400 million people living with hepatitis B (HBV) and/or C virus (HCV) infections worldwide. This situation is relevant because both viruses can be transmitted vertically (VT). Despite efforts to prevent VT, many measures still need to be reinforced, especially regarding the spread of clinically relevant viral variants. Therefore, this study aimed to demonstrate the clinical/laboratory profile of pregnant women identified as positive for HBV and HCV during prenatal care, and referred to a specialized viral hepatitis unit in Rio de Janeiro between 2016-2022, and to identify those with clinically relevant mutations that can be transmitted vertically. Patients / Materials and Methods: To this end, all pregnant women with positive rapid tests were retested by eletrochemioluminescence using commercial tests for HBV antigens and antibodies against HBV and HCV. In addition, molecular tests were carried out to quantify HBV DNA and/or HCV RNA. Liver enzyme tests were also carried out in order to classify pregnant women according to HBV clinical phase. Results and Discussion: Two hundred and thirty-two pregnants women with HBV and HCV infection were analyzed. Among the 138 pregnant women with HBV, 95% had HBeAg-negative chronic infection and the mean viral load was 3.70 log IU/ml. Up to now, 6 samples were sequenced, Genotypes A1 (n=5/6,83%) and D3 (n=1/6,16%) were identified and the mutation Y100C was found. In 94 pregnant women with HCV, 75.7% had HCV RNA successfully amplified, with subtypes 1a (n=12/33; 36,4%), 1b (n=17/33; 51,5%) and 3a (n=3/33; 9,1%) detected. Clinically relevant mutations were found V321L, V321IV, C316N. Conclusions: Identifying mutations in HBV and HCV infections is crucial for epidemiological surveillance and postpartum treatment. Our findings highlight the importance of monitoring drug-resistant mutations in pregnant women with these infections.